Implementasi Hukum Benford sebagai Alat Deteksi Kecurangan Laporan Keuangan pada Kasus PT. Indofarma Tbk (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to analyze potential fraud in the financial statements of PT Indofarma Tbk by employing Benford’s Law as a forensic detection tool. Benford’s Law is a statistical theory that explains the natural distribution of the first digits in a numerical dataset, which can be utilized to detect anomalies that may indicate manipulation. The data used in this research consist of the annual financial statements of PT Indofarma Tbk for the period 2018–2022. The analysis was conducted by calculating the first-digit distribution of each financial statement item and comparing it with the theoretical distribution predicted by Benford’s Law. The Chi-Square statistical test was applied to examine the significance of deviations between the actual and theoretical distributions. The results reveal significant deviations in certain years, particularly in specific accounts that would normally be expected to follow the natural digit distribution. These deviations suggest potential irregularities in the presentation of financial figures. Although Benford’s Law does not directly prove fraud, the detected deviations serve as early warning signals (red flags) for auditors and regulators to conduct further investigation. This study underscores the importance of forensic accounting and early detection methods in preventing and identifying fraudulent financial reporting, especially in publicly listed pharmaceutical companies that play a strategic role in healthcare services. Therefore, Benford’s Law can be considered an effective tool to enhance transparency and accountability in corporate financial reporting.